Strategies for Driving the Future of Educational Building Design in Terms of Indoor Thermal Environments: A Comprehensive Review of Methods and Optimization - Shihai Wu; Pengzhi Zhou; Ying Xiong; Chengye Ma; Dizi Wu; Weizhen Lu (Buildings)
This comprehensive review critically examines current methodologies and optimization strategies for designing indoor thermal environments in educational buildings amid the challenges of global climate change and energy demands. The paper evaluates existing research methods, such as numerical simulations, data-driven models, and field measurements, revealing significant limitations in addressing the complex and dynamic nature of educational environments. It highlights the overemphasis on energy efficiency while neglecting user comfort and individual differences, such as students’ physiological and psychological needs. The review underscores the necessity of integrating human-centered design strategies, climate adaptability, and interdisciplinary approaches to improve building performance and enhance student well-being. Future research should focus on developing multimodal data fusion frameworks, applying AI-based optimization, and incorporating emerging technologies like BIM and IoT for dynamic management. By advocating for more adaptable and sustainable thermal environment strategies, this study provides a foundation for advancing educational building design in response to climate change and energy crises.